Finding presence of the God in investor’s heart: examining the link between religiosity and socially responsible investment - Tegar Satya Putra; Marwan Asri (Jurnal Siasat Bisnis, 2019)
Socially Responsible Investment or ethical investment has grown significantly in various countries. This rising trend creates a big question mark in the head of investors and finance scholars as the concept of ethics and investment has not been widely discussed in the finance literature. The discussion mostly focuses on the demographic characteristics of socially responsible investors and there is only a handful of literature which discusses the within-person factors that influence an investor to invest in SRI. Based on those notions, this paper examines the relationship between investors’ religiosity with their decision-making process in SRI. Religiosity is chosen as the possible antecedent because religiosity has discussed widely in the business ethics literature as one major antecedent in an ethics-related construct. It is found that Religiosity does influence investors decision-making process indirectly through their decision frame.